Factors Affecting Company Value: : A Study of Real Estate and Property Companies Listed on the IDX - Fajariyanti, Indah Ayu; Lulu Nurul Istanti (Adpebi International Journal of Multidisciplinary Sciences, 2023)
Purpose – This paper seeks to test and analyze the effect of return on assets, current ratio, and debt to equity ratio on the value of real estate and property companies listed on the IDX for five-year time frame. Methodology/approach – This research was a quantitative study. The sample of this study was taken using purposive sampling techniques with the following criteria, the first is a real estate and property company that publishes financial statements that have been audited consecutively during the 2015-2019 period, and the second is a real estate and property company whose financial statements contain all the variables needed in the study. The analytical tools in this study are multiple linear regression analysis. Findings –Based on the results of research on the multiple regression model, the return on assets and debt to equity ratio have a significant positive effect on price to book value. Meanwhile, the current ratio has no significant effect on the price to book value. Novelty/value – Price to Book Value shows how far the company is able to create company value relative to the amount of capital invested. The higher the Price to Book Value ratio, the more successfully the company creates value for shareholders.